Potential toxicity effects of Gurgem injection on prenatal development of wistar rats (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Safflower (Carthamus tinctorius) has long been used to treat cardiovascular diseases. In this study, an injectable formulation of Carthamus tinctorius (CTI) was developed. Beyond its pharmacological benefits, potential toxicity must be thoroughly assessed. Previous studies have reported possible maternal, fetal, and teratogenic toxicities in rodents, while also suggesting fertility-enhancing properties, underscoring the need for further investigation.Aim: This study aimed to evaluate the potential toxicity effects of CTI in pregnant Wistar (Han) rats and their developing fetuses. The research followed OECD Guideline No. 414, the international standard for prenatal developmental toxicity testing.Methods: Pregnant rats were randomly divided into four groups (n=3 females/group): a control and three treatment groups receiving CTI at doses of 0.45 (low), 0.82 (medium), and 1.65 ml/kg (high). CTI was administered daily via intramuscular injection from gestational day (GD) 6 to 20. On GD21, cesarean sections were performed. Maternal parameters (body weight gain, ovaries with HE staining, corpora lutea count, and uterine examination) and fetal parameters (body weight, head cranium, tail length, placental weight) were evaluated.Results: Corrected maternal weight gain and fetal body weight were significantly reduced in low- and high-dose groups compared to the control. Increased anogenital distance index and congenital abnormalities, such as hydrocephalus, were observed in some fetuses. Conversely, the 0.45 ml/kg group showed improved embryonic survival and no significant treatment-related adverse effects.Conclusion: The study identified a monotonous dose-response curve (MDRC), showing increasing adverse effects with higher CTI doses. The lowest observed adverse effect level (LOAEL) was 0.45 ml/kg, and the no observed adverse effect level (NOAEL) was also determined at 0.45 ml/kg, suggesting limited safety margins for CTI use during pregnancy.